Bullying Climate and School Engagement in Ninth‐Grade Students. (18th December 2012) - Mehta, Sharmila B.; Cornell, Dewey; Fan, Xitao; Gregory, Anne
Abstract : BACKGROUND: Many authorities agree that bullying has a widespread impact on school climate, affecting bystanders as well as victims. This study tested the contention that a climate of bullying can have a schoolwide impact on student engagement in school. METHODS: Hierarchical linear modeling assessed the relations between student perception of bullying climate and student engagement at the individual and school level in a statewide sample of 7058 ninth graders randomly selected from 289 schools participating in the Virginia High School Safety Study. Student engagement was assessed by self‐report scales measuring commitment to school and involvement in school activities. RESULTS: Individual differences in perception of school climate characterized by bullying were associated with lower commitment to school, but not less involvement in school activities. School‐level differences in student perceptions of bullying climate were associated with both lower commitment to school and less involvement in school activities, after controlling for the effects of gender, race, school size, proportion of ethnic minority students in the school, and individual‐level perception of bullying climate. CONCLUSION: Efforts to improve student engagement should consider the schoolwide impact of bullying on all students.